The Effect of Investment Risk on Stock Returns in Companies Listed on The LQ-45 Index - Nurman; Ramli, Anwar; Lestari Musa, Dwi Anugerah; Asniwati (PT. Maju Malaqbi Makkarana, 2024)
This study aims to analyze the effect of investment risk on stock returns for the LQ45 index for the 2016-2021 period. This research uses quantitative methods. Sampling using several criteria so that the data obtained were 27 companies. The analysis technique used is simple linear regression analysis using the SPSS version 22 program. The results of this study indicate that the significance value is 0.781> 0.05 and the coefficient is 0.008, which means that Beta has a positive and insignificant effect on stock returns. The results of this study do not support the hypothesis that has been put forward.